2014
DOI: 10.1192/pb.bp.113.044388
|View full text |Cite
|
Sign up to set email alerts
|

Delayed discharge from intellectual disability in-patient units

Abstract: Aims and method We undertook a cross-sectional service evaluation of the reasons and extent of delay in the discharge process in an intellectual disability hospital over a 12-month period. Delays at each stage of the discharge process are also quantified in this study.Results We found that discharge was delayed for 29% of patients during the study period. The majority (78.5%) was due to awaiting completion of assessment of future care needs and waiting for public funding.Clinical implications Commissioners (he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 6 publications
1
40
0
Order By: Relevance
“…The following exclusion criteria were also applied to the articles identified through the database search: research focusing on mental health, maternal and child and adolescent health, and palliative care was excluded; delays may occur in those settings for different reasons, for example relapse of mental health disorders, and consequently, delays due to non‐medical reasons are difficult to determine . Abstracts, editorials, commentaries and book reviews were excluded because the review focused on primary research.…”
Section: Methodsmentioning
confidence: 99%
“…The following exclusion criteria were also applied to the articles identified through the database search: research focusing on mental health, maternal and child and adolescent health, and palliative care was excluded; delays may occur in those settings for different reasons, for example relapse of mental health disorders, and consequently, delays due to non‐medical reasons are difficult to determine . Abstracts, editorials, commentaries and book reviews were excluded because the review focused on primary research.…”
Section: Methodsmentioning
confidence: 99%
“…This goes together with the inevitable negative financial implications typically incurred -Intermediate care and 72-hours discharge target (Levin & Crighton, 2019) in such situations. [26][27][28][29] In England, there were on average 4000 patients a day who experienced some form of delay in transfer of care between 2013 and 2016. 30 This translated to approximately 115 000 bed days' worth of delayed care.…”
Section: Causes and Effects Of Delayed Dischargesmentioning
confidence: 99%
“…The impact of cost on acute hospital settings in the absence of such services is particularly pronounced 10,57 due to the bedblocking effects inevitably incurred. 5,28,58 An additional two more recent systematic reviews pertaining to cause and effect of delayed discharges were analysed. One such review 59 chose to tackle delayed discharges from a prevalence and cost perspective.…”
Section: Effects Of Delayed Discharges/interventionsmentioning
confidence: 99%
“…7,8 Once in hospital, they are more likely to remain despite being deemed ready for discharge. 9 They are also more likely to be admitted into long-term care (LTC) facilities at a younger age, 10 and to die earlier. 11 It has been suggested that when individuals also have a mental health and/or addiction (MHA) disorder in addition to their disability, they encounter further complications with healthcare use.…”
Section: Introductionmentioning
confidence: 99%